Hubungan Kadar Kolesterol Dan Indeks Masa Tubuh Terhadap Kejadian Hipertensi Di Laboratorium Klinik Prodia Bengkulu Tahun 2022 - Lenzu, Hendrek Miko; Nurdan, Jon Hendri; Sianipar, Berlian Kando (Universitas Dehasen Bengkulu, 2022)
Hypertension is a condition in which there is an increase in systolic blood pressure ≥140 mmHg and/or diastolic blood pressure ≥90 mmHg (RI Ministry of Health, 2019). Data released by WHO (2018) shows that around 26.4% of the world's population has hypertension with a ratio of 26.6% of men and 26.1% of women. In Indonesia, the estimated number of cases of hypertension in Indonesia is 63,309,620 people, while the death rate in Indonesia due to hypertension is 427,218 deaths. Hypertension occurs in the age group 31-44 years (31.6%), age 45-54 years (45.3%), age 55-64 years (55.2%) (Riskesdas RI Ministry of Health, 2018). Based on data from the 2018 Bengkulu Province Health Profile, it is estimated that there are 889,010 sufferers who have hypertension in Bengkulu province and only 9% receive services or utilize health services according to standards (Bengkulu Provincial Health Office, 2019). This study used a quantitative method with a cross-sectional research design. The population in this study were all patients seeking treatment at the Prodia Bengkulu Clinical Laboratory in 2022, totaling 1,426 patients. The sample used in this study were 93 respondents. The results of this study indicate that there is a relationship between cholesterol levels and the incidence of hypertension at the Prodia Bengkulu Clinical Laboratory in 2022. Viewed using the Chi-Square test (Pearson Chi-Square), a value of 9.265 is obtained with a value of p = 0.010 and there is a relationship between body mass index and the incidence of hypertension in Prodia Bengkulu Clinical Laboratory in 2022 viewed using the Chi-Square test (Pearson Chi-Square) obtained a value of 9.783 with a p value = 0.021 Suggestions can contribute information to the public, regarding the relationship between cholesterol levels and Body Mass Index with hypertension in Bengkulu City and for people with hypertension to be able to check and carry out routine checks in the laboratory